Suppression of Basal Spontaneous Gonadotropin-Releasing Hormone Neuronal Activity during Lactation: Role of Inhibitory Effects of Neuropeptide Y - Xu, Jing (The Endocrine Society, 2009)
Increased neuropeptide Y (NPY) activity drives the chronic hyperphagia of lactation and may contribute to the suppression of GnRH activity. The majority of GnRH neurons are contacted by NPY fibers, and GnRH cells express NPY Y5 receptor (Y5R). Therefore, NPY provides a neurocircuitry for information about food intake/energy balance to be directly transmitted to GnRH neurons. To investigate the effects of lactation on GnRH neuronal activity, hypothalamic slices were prepared from green fluorescent protein-GnRH transgenic rats. Extracellular loose-patch recordings determined basal GnRH neuronal activity from slices of ovariectomized control and lactating rats. Compared with controls, hypothalamic slices from lactating rats had double the number of quiescent GnRH neurons (14.51 ± 2.86 vs. 7.04 ± 2.84%) and significantly lower firing rates of active GnRH neurons (0.25 ± 0.02 vs. 0.37 ± 0.03 Hz). To study the NPY-postsynaptic Y5R system, whole-cell current-clamp recordings were performed in hypothalamic slices from control rats to examine NPY/Y5R antagonist effects on GnRH neuronal resting membrane potential. Under tetrodotoxin treatment, NPY hyperpolarized GnRH neurons from −56.7 ± 1.94 to −62.1 ± 1.83 mV; NPY’s effects were blocked by Y5R antagonist. To determine whether increased endogenous NPY tone contributes to GnRH neuronal suppression during lactation, hypothalamic slices were treated with Y5R antagonist. A significantly greater percentage of GnRH cells were activated in slices from lactating rats (52%) compared with controls (28%). These results suggest that: 1) basal GnRH neuronal activity is suppressed during lactation; 2) NPY can hyperpolarize GnRH neurons via postsynaptic Y5R; and 3) increased inhibitory NPY tone during lactation is a component of the mechanisms responsible for suppression of GnRH neuronal activity.